2005
DOI: 10.1002/hup.717
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 levels decrease with SSRI treatment in patients with major depression

Abstract: The results of this study suggest that proinflammatory cytokines show some changes during the course of treatment of major depression. These findings might also be considered as supporting the hypothesis of a modulatory role of antidepressants on the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(121 citation statements)
references
References 24 publications
4
115
1
1
Order By: Relevance
“…2004; Dunn et al, 2005;Castanon et al, 2002;Sluzewska et al, 1996;Basterzi et al, 2005). These results imply that depression could be a low-grade systemic inflammatory condition.…”
mentioning
confidence: 86%
“…2004; Dunn et al, 2005;Castanon et al, 2002;Sluzewska et al, 1996;Basterzi et al, 2005). These results imply that depression could be a low-grade systemic inflammatory condition.…”
mentioning
confidence: 86%
“…133 Sacre et al 134 reported that fluoxetine and citalopram reduced inflammation by inhibiting TLR function. Elevated cytokine levels in depressed patients have also been shown to normalize following SSRI treatment; 135,136 however, normalization of cytokine levels appears not to occur in patients that did not respond to SSRIs, 137 raising the possibility that immune system status could be a useful biomarker in structuring personalized depression therapies. Since T cells appear not to express SERT 47 (though note the caveat mentioned regarding T cell subtypes above), they do express 5-HT receptors 47 and thus the effects of SSRIs in vivo may also be indirect.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%
“…195 In microglial and in mixed glial cultures, amitriptylin and nortriptylin were observed to inhibit the release of IL-1b and TNF-a. 196 Regarding the serum levels of MD patients, several researchers reported a decrease of IL-6 during treatment with serotonin re-uptake inhibitors 197,198 and other antidepressants. 101 Myint et al 85 reported an increase of the regulating, anti-inflammatory Th3-cytokine TGF-b together with a reduction of the IFN-g/IL-4 ratio after antidepressant therapy.…”
Section: Antidepressant Pharmacotherapymentioning
confidence: 99%